Functionalization and metallization of diamondoids - Gunawan, Maria Agatha E.; Justus Liebig University Giessen (My University, 2015)
The thesis deals with development of synthetic methods for preparation of novel carbon-metal organohybrid based on diamondoid and palladium. The vapor pressure of various diamondoids was measured from a new measurement protocol at solid-vapor thermodynamic equilibrium state. Their volatile tendency opened a possibility to do deposition from gas phase and at various pressure (ambient, primary vacuum, and high vacuum) of diamondoids on silicon or mica substrates. SEM observations have shown that depending on the type of functional groups on the diamondoid, different crystal shapes can be produced (rods, needles, triangles, truncated octahedral form).OMCVD of palladium on functionalized diamantanes showed that Pd deposition occurs preferentially on the oxide native layer on silicon substrates than on diamondoid crystals bearing hydroxyl or fluorine groups. This urged the synthesis new diamondoids with phosphino groups in order to make strong covalent bonding between the modified diamondoid and palladium.A full set of functionalized diamondoid phosphines were synthesized with unexpected air-stability of some primary diamondoid phosphines were observed.It has been shown that the use of P(III) phosphine as anchoring sites allowed the formation of hybrid material Pd@PH2-Diam-OH. Different characterizations (XPS, SEM, TEM, and EDX) indicated that an insulator material Pd@PH2-Diam-OH formed during the CVD deposition with P-Pd interaction.

Ces travaux de thèse développent des méthodes pour la synthèse de nouveaux organohybrides carbone-métal basés sur les diamantoïdes et le palladium.Les pressions de vapeur de divers diamantoïdes ont été mesurées grâce à un protocole original de mesures de l´état d´équilibre thermodynamique solide-vapeur. Leur relative volatilité a permis de réaliser des dépôts de diamontoïdes en phase vapeur, à diverses pressions (ambiante, vide primaire, et vide poussé) sur des substrats comme le silicium ou le mica. Les observations au MEB ont montré que, selon le type de groupes fonctionnels présents sur le diamantoïde, différentes formes cristallines peuvent être produites (tiges, aiguilles, triangles, formes octaédriques tronquées).L´OMCVD de palladium sur les diamantanes fonctionnalisés montre que le palladium se dépose préférentiellement sur le substrat du silicium plutôt que sur les cristaux de diamantoïdes portant des groupes hydroxy ou fluor. Nous avons alors envisagé la synthèse de nouveaux diamontoïdes portant des groupes phosphino, qui pourraient former une liaison covalente entre le diamontoïde modifié et le palladium.Un ensemble complet de diamondoïdes fonctionnalisés par des phosphines a été synthétisé. Certaines nouvelles phosphines primaires ont révélées une stabilité à l´air inattendue.Il a été montré que l´utilisation de phosphine P(III) comme sites d´ancrage a permis la formation du matériau hybride Pd@PH2-Diam-OH. Différents caractérisations (XPS, MEB, MET, et EDX) ont montré que le matériau Pd@PH2-Diam-OH formé est isolant, et présente des interactions Pd-P.
Funktionalisierung und Metallisierung von Diamantoide
Keywords: Pd OMCVD; hybrid material; functionalized diamondoids; organic self-assembly; air-stable phosphine; ddc:540